2021
DOI: 10.1038/s41598-021-91142-1
|View full text |Cite
|
Sign up to set email alerts
|

Confirming putative variants at ≤ 5% allele frequency using allele enrichment and Sanger sequencing

Abstract: Whole exome sequencing (WES) is used to identify mutations in a patient’s tumor DNA that are predictive of tumor behavior, including the likelihood of response or resistance to cancer therapy. WES has a mutation limit of detection (LoD) at variant allele frequencies (VAF) of 5%. Putative mutations called at ≤ 5% VAF are frequently due to sequencing errors, therefore reporting these subclonal mutations incurs risk of significant false positives. Here we performed ~ 1000 × WES on fresh-frozen and formalin-fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Patients were categorized as high mKRAS or low mKRAS if they had KRAS mutant allele frequencies greater than or less than 20%, respectively. Traditionally, allele frequency cut‐offs are set at 5% 39–41 . Previous studies looking at KRAS‐mutant tumor heterogeneity found that average KRAS mutation frequencies were between 10% and 20% 42 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were categorized as high mKRAS or low mKRAS if they had KRAS mutant allele frequencies greater than or less than 20%, respectively. Traditionally, allele frequency cut‐offs are set at 5% 39–41 . Previous studies looking at KRAS‐mutant tumor heterogeneity found that average KRAS mutation frequencies were between 10% and 20% 42 .…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, allele frequency cut-offs are set at 5%. [39][40][41] Previous studies looking at KRAS-mutant tumor heterogeneity found that average KRAS mutation frequencies were between 10% and 20%. 42 Twenty percent (20%) was chosen as our allele frequency cutoff as the distribution of the KRAS allele frequencies in our sample were more dispersed near this cut-off of 10% and 20%.…”
Section: Definition Of Kras Mutant Allele Frequency and Analysis Thre...mentioning
confidence: 99%
“…Interestingly, RNA VAF was significantly higher than DNA VAF within expressed mutations of RNA–DNA overlap part ( Figure 5C right comparison, p < 1 e-5), suggesting an expression tendency for the mutant allele. The common cancer WES study has a mutation limit of detection (LoD) at 5% VAF, and reporting these subclonal mutations incurs the risk of sequencing error–induced false positives ( Yan et al, 2021 ). For these low-VAF (<0.05) DNA somatic mutations, their RNA VAFs were much higher, with median values of 0.374 in LUSC, 0.342 in BLCA, and 0.241 in GBM.…”
Section: Resultsmentioning
confidence: 99%
“…The competitive hybridization reaction enables PCR not only to sensitively recognize and selectively amplify SNVs, but also to do so across a broad temperature window spanning 8 • C, thus conveniently accomplishing multiplexing purposes. Several BDA-derived methods showed high sensitivity to detect low-abundant ctDNA mutations with cost-effective experimental procedures (49)(50)(51)(52). Therefore, we believe that these kind of technologies are quite appropriate to implement a highly sensitive, multiplexingenabled, and cost-effective MRD detection system for NSCLC.…”
Section: Introductionmentioning
confidence: 99%